Influence of push and pull techniques on high-speed buried-arc gmaw process - Dreveck N.W.* (2020)
© 2020, University Federal de Uberlandia. All rights reserved.The GMAW torch orientation, whether pulling or pushing, influences both arc welding and hybrid processes. In hybrid laser-arc welding, for example, when the torch is pulled, a greater bead penetration is obtained. To promote greater penetration, the literature also indicates the use of a buried arc in GMAW, although it was initially developed to only operate with a vertically-positioned torch. Therefore, this work aims to investigate the influence of the push and pull techniques on the behavior of buried-arc GMAW at high welding speeds. Welds were performed with the push and pull techniques under the following conditions: buried and unburied (long) arc with welding speeds of 1.0, 1.5 and 2.0 m/min and current ranging from 450 to 470 A. The process tends to be more stable when pulling than when pushing (buried or long arc). Evidence of instability was only identified for the pushed buried arc, due to material accumulation at the front region of the molten pool, for the higher welding speeds. Only the 1.0 m/min buried-arc processes resulted in beads with an appropriate surface finish.